Evaluation of Cultural Content on English Module of 9th Grade Students Published by Indonesia"™s Government during the Covid-19 Pandemic - Damayanti, Tiara (Proceedings International Conference on Teaching and Education (ICoTE), 2024)
The Covid-19 Pandemic affects all sectors in every side of the world. The education side is also becoming one of the most affected areas due to this situation. Indonesia"™s government made a regulation for conducting distance learning almost in the past two years. By creating this regulation, they also made a module for the teachers and students with the aim of facilitating the education field so it could achieve the materials planned in the general syllabus of Indonesia"™s curriculum even though they have to do distance learning. The cultural content is usually found in the English module or textbooks. Culture as one of the national identities should be taught to the students as young as they are. There are three categories of cultural content as follows: source culture, target culture, and international target culture. The descriptive qualitative method will be used in this study since it is aimed to classify and evaluate the cultural content found in the English module used by the 9th grade students in Indonesia and discuss the most appropriate culture that should be taught to junior high school students when it comes to the education in the digital age. The findings of this study show that most cultural categories occurred is from the target culture that is the US and UK culture followed by the source culture. Then, the most cultural elements found in the English module are in a form of product, person, and practice in a line. There is no perspective element found in this study. Since the aim of learning by using this module is for mastering the target language (English), it is acceptable when the target culture is easier to find compared to the source or international target culture. The need of module evaluation here hopefully can help the teachers to select the appropriate sources for the teaching and learning materials in the English classroom, especially in junior high school.